Conventional Pedagogies in EFL Higher Education: A Critical Inquiry into Lecturers’ Beliefs and Student Voices - Bagus Surya Muhammad; Rahmat Setiawan (Institut Agama Islam Negeri Palopo, 2025)
Conventional teaching methods, such as grammar-translation and learning through memorisation, summarisation and lectures are still often applied in learning English as a foreign language (EFL). However, the effectiveness of these methods in improving students' language proficiency is still a matter of discussion. This study aims to examine teachers views on conventional teaching methods in EFL and their effects on students’ participation, enthusiasm and learning outcomes. This study applied a qualitative approach through interview techniques. Information was obtained from six EFL students who had experience of traditional methods in their classes. Data were analyzed through thematic method to find the main patterns in the teachers' views and experiences. The findings indicated that the traditional method was successful in improving students' grammar comprehension and writing skills. However, many teachers recognized that this approach is not effective in improving students' speaking and listening skills. In addition, traditional approaches often lead to boredom and lack of student participation in learning activities. Thus, many teachers choose to combine traditional methods with communicative approaches or technology to enhance the learning effect. This study recommends the application of blended learning methods that integrate grammar structures with active communication exercises to produce more interesting and effective learning for EFL students.